Alternatif Model Partisipatif Didalam Pemberdayaan Konsumen Cerdas Di Desa Gondangrejo, Kecamatan Windusari, Kabupaten Magelang - Rani Pajrin; RR Yunita Puspandari; Fathiya Nabila (Politeknik Negeri Cilacap, 2021)
Consumers' awareness in Indonesia in fighting for consumer rights is still relatively low, which can be seen from the Consumer Empowerment Index which is still lagging behind other European countries. Community service activities carried out in Gondangrejo Village, Windusari District, Magelang Regency are carried out by providing socialization and education about the importance of being a smart consumer who is aware of the rights and obligations of consumers. Rights and obligations are regulated in Law Number 8 of 1999 concerning Consumer Protection. The method used in this activity is a Participatory Alternative Model which uses Environmental Scanning, through the author's method of building the ability to view programs on an ongoing basis through mapping of related stakeholders. The purpose of this service activity is the participation of the community as consumers so that consumers can fulfill their rights as consumers. On the other hand, the smart consumer group can increase the national consumer empowerment index.